Providing an extended use of an otological‐specific outcome instrument to derive cost‐effectiveness estimates of treatment. (December 2015) - Frew, E.J.; Harrison, M.; Rossello Roig, M.; Martin, T.P.C.
Abstract : Objectives: Although quality‐adjusted life years (QALYs) are increasingly being used by decision‐makers to make comparisons of cost‐effectiveness, there are no otological‐specific outcome measures that fit within this QALY framework. This study had two main objectives. The first was to provide a means to derive QALYs from a condition‐specific otological instrument (Cambridge Otology Quality of Life, COQOL), and the second was to assess the convergent validity, or degree of correlation, between the COQOL and SF‐6D, an established QALY instrument. Design: Longitudinal cohort study designed to assess the convergent validity between SF‐6D and COQOL and to generate a mapping function to enable SF‐6D values to be predicted from the COQOL responses. Setting: Cambridge University Hospital, UK. Participants: A total of 207 patients attending a routine outpatient general otology clinic. Main outcome measures: SF‐6D and the COQOL instrument completed at baseline and again 3 months later. Results: Convergent validity was demonstrated with mean SF‐6D values decreasing linearly with increasing severity on the COQOL instrument. Overall, the correlation between the COQOL scores and the SF‐6D values was moderate and statistically significant ( r = 0.490, P = <0.001). A simple mapping model based on an ordinary least squares (OLS) regression function predicted SF‐6D values from the COQOL data with a reasonable degree of accuracy. Further validation using the follow‐up 3‐month data confirmed the prediction power of this mapping model. Conclusions: This study provides a method for estimating QALYs from condition‐specific COQOL data and provides the opportunity for the cost‐effectiveness of otological treatment to be measured and placed within the national QALY framework.